(untitled) - Wild, John J. (Boston, MA., 2005)
FINANCIAL ACCOUNTING: Information for Decisions, 3e, by Wild addresses the topics and issues typically covered in Financial Accounting while at the same time motivating student interest in accounting through its extensive use of entrepreneurial examples, application of analysis skills, integration of interactive tutorial software, and a highly engaging pedagogical design. This is the only textbook in the financial accounting market that thoroughly integrates ideas and practices followed by today's business entrepreneurs, speaking more directly to students and better preparing them for the workforce they will enter.
Keywords: Accounting